Using Community Engagement to Inform and Implement a Community-Randomized Controlled Trial in the Anishinaabek Cervical Cancer Screening Study - Wood, Brianne; Burchell, Ann N.; Escott, Nicholas; Little, Julian; Maar, Marion; Ogilvie, Gina; Severini, Alberto; Bishop, Lisa; Morrisseau, Kyla; Zehbe, Ingeborg (Frontiers in Oncology, 2014)
Social, political, and economic factors are directly and indirectly associated with the quality and distribution of health resources across Canada. First Nations (FN) women in particular endure a disproportionate burden of ill health in contrast to the mainstream population. The complex relationship of health, social, and historical determinants are inherent to increased cervical cancer in FN women. This can be traced back to the colonial oppression suffered by Canadian FN and the social inequalities they have since faced. Screening - the Papinacolaou (Pap) test – and early immunization have rendered cervical cancer almost entirely preventable but despite these options, FN women endure notably higher rates of diagnosis and mortality due to cervical cancer. The Anishinaabek Cervical Cancer Screening Study (ACCSS) is a participatory action research project investigating the factors underlying the cervical cancer burden in FN women. ACCSS is a collaboration with 11 FN communities in Northwest Ontario, Canada and a multidisciplinary research team from across Canada with expertise in cancer biology, epidemiology, medical anthropology, public health, virology, women’s health, and pathology. Interviews with healthcare providers and community members revealed that prior to any formal data collection education must be offered. Consequently, an educational component was integrated into the existing quantitative design of the study: a two-armed, community-randomized trial that compares the uptake of two different cervical screening modalities. In ACCSS, the Research Team integrates community engagement and the flexible nature of participatory research with the scientific rigor of a randomized controlled trial. ACCSS findings will inform culturally appropriate screening strategies, aiming to reduce the disproportionate burden of cervical disease in concert with priorities of the partner FN communities.